HUKUM KARMA PHALA DALAM CERITA SANTAPTAKA DAN PARA HANTU (GARUDA PURANA): Perjalanan Santaptaka - Ongen lehalima (Jawa Dwipa, 2026)
The Law of Karma Phala is one of the fundamental teachings in Hinduism, emphasizing that every human action produces corresponding consequences, whether good or bad. This concept plays an important role in shaping moral and ethical values among Hindus. One medium for conveying the teachings of Karma Phala is found in mythological narratives contained in the Purana scriptures, particularly the Garuda Purana. This article aims to examine and analyze the concept of the Law of Karma Phala in the story of Santaptaka and the Ghosts through the perspective of Hindu literary (Susastra Hindu) studies. The research employs a qualitative method with a descriptive-analytical approach through a literature review of the Garuda Purana and supporting Hindu scriptures such as the Wrhaspati Tattwa, Slokantara, and Nitisastra. The findings indicate that the stories of Paryusita, Sucimukha, Sighraga, Rodhaka, and Lekhaka represent a clear application of the Law of Karma Phala, in which acts of Asubha Karma influenced by Tri Guna and Tri Mala result in their rebirth as preta (ghosts). Furthermore, the narrative emphasizes the importance of self-control, the cultivation of Sattwam, and moral awareness as fundamental principles in leading one’s life. Thus, the story of Santaptaka and the Ghosts is not merely mythological in nature but also contains moral and spiritual educational values that are relevant as behavioral guidelines for Hindus in daily life.